Sosialisasi Cara Menulis Sitasi dan Daftar Pustaka pada Mahasiswa Program Studi Pendidikan Matematika - Baiq Rika Ayu Febrilia; Novia Alifah Fauzia; Siti Harni Astuti; Ni Made Wirastika Sari; Idiatul Fitri Danasari; Sri Mulyawati (Cv. Utility Project Solution, 2023)
Citation is a reference or usually also known as a quote that allows the author to provide recognition for the reference sources that have been cited. Citation writing is needed to strengthen one's argument against the results of his research. However, writers often make mistakes in writing citations and bibliography. This happens a lot, especially among students of the Mathematics Education Department at Universitas Pendidikan Mandalika. This service activity aims to increase students' understanding of how to write citations and bibliography. Community service activities were carried out online for one day with 14 student participants. The method used is the lecture and question and answer method, in which the stages of the activity are divided into four stages, namely the planning, registration, implementation and evaluation stages. The instruments used in this activity were a questionnaire regarding participants' understanding of writing citations and a bibliography developed in the form of a Google form and given before and after the community service activities. The results of the community service activities showed that there was an increase in students' understanding of writing citations and bibliography. This increase can be seen from the results of the comparison of the participants' pre-test and post-test results.